Presidents and democracy in Latin America
1 online resource
Keywords: This new textbook provides students with a comprehensive and accessible introduction to the presidents and presidential leadership in Latin America. Unlike other texts, Presidents and Democracy in Latin America integrates both political analysis and major theoretical perspectives with extensive country-specific material. Part One examines the developments in recent years in Latin American presidentialism and identifies different characteristics of society and politics which have influenced Latin American governments. The personalization of political life and of presidential government help to illustrate the character of Latin American politics, specifically on the type of political career of those who occupied the presidential office, the leadership style of these presidents and the type of government which they led. Part Two studies two presidents in each of six countries in the region which reflect the broad trends in the political and electoral life: Argentina, Brazil, Chile, Colombia, Mexico, and Peru. Each case study first provides the biographical background of the president; it outlines the political career of the president both inside and outside of a party, including at the local level; the popularity of the president at the time of the presidential election is given, as well as the mode of selection of the candidates (selection by party leaders only, by party members or by a primary). The relation of the president with the government or ministers, especially if there is a coalition government, is detailed. This textbook will be essential reading for all students of Latin American Politics and is highly recommended for those studying executive politics, political leadership, and the state of democratic governance in Latin America.